PENGGUNAAN “AUTOMATIC FEEDER” PADA PENDEDERAN IKAN KERAPU TIKUS (Cromileptes altivelis) - Wiwie Soemarjati; Veni Damayati; Yani Lestari; Mizab Asdari (Samakia : Jurnal Ilmu Perikanan, 2013)
Seeds of humpback grouper are often nursery is the size of 3 cm, to feed for nursery use artificial feed or pellets. Feed pellets are in great demand by employers nursery, this is because the artificial feed (pellets) nutritionally complete, easy to obtain, not depending on the season, easy in giving, does not require much effort to chop up trash fish and does not contaminate the media maintenance. Obstacles often faced in the nursery humpback grouper is an artificial feeding system gradually by feeding manually little by little until the fish are fed. Feeding system requires a lot of effort and a long time, making it less practical. The purpose of this engineering is to get the technique of feeding "Automatic Feeder" on nursery humpback grouper. Goal of this engineering is to obtain SR more than 95%, the growth rate is better and the efficiency of the use of labor. The results showed that - Survival Rate (SR) maintenance by using automatic feeder of 98.25%. Daily growth of fish feed administration using a automatic feeder for 0.01965 gram / day and FCR of 1.48. In the nursery unit of humpback grouper should use tools that SR increased automatic feeder, feeding on time, not a lot of energy providers dobutuhkan feed and feed can be set so as to be more efficient and effective.